Extracellular matrix metalloproteinases in the etiopathogenesis of endometriosis: a systematic review and critical appraisal - M. Ζafrakas; Κ. Κοtronis; P. Papasozomenou; P. Eskitzis; G. Grimbizis (Clinical and Experimental Obstetrics & Gynecology, 2020)
Despite extensive research in the field, the etiopathogenesis of endometriosis remains an unresolved enigma. The possible role of different enzymes of the extracellular matrix, in particular the role of the matrix metalloproteases or metalloproteinases (MMPs) in the etiopathogenesis and the mechanisms involved in the processes of benign dissemination of endometriosis have been widely investigated in recent years. Various members of the enzymatic system of the MMPs, as well as their inhibitors, termed tissue inhibitors of metalloproteinases (TIMPs) and their inducer, termed extracellular matrix metalloproteinase inducer (EMMPRIN), have been implicated in the mechanisms involved in endometriosis formation, progression, and maintenance. The aim of the present paper was to provide an overview and critical evaluation of existing experimental evidence on this issue. For this purpose the authors have conducted a systematic review of the literature and evaluated relevant papers regarding experimental animal models, in vitro experiments, and analyses in human samples and studies regarding genetic polymorphisms in humans. In conclusion, members of the system of matrix MMPs, their inhibitors and inducers could be useful as novel diagnostic and prognostic biomarkers in determining the severity of endometriosis and response to therapy. Furthermore, in depth knowledge in this field could possibly lead to the development of more efficient treatment modalities. Future research should focus on the systematic investigation of the entire MMPs system in endometriosis, as well as on the interaction between its members.